Tanggung Jawab Hukum Notaris atas Perbedaan Isi Minuta Akta dan Salinan Akta dalam Prinsip Kehati-Hatian - Helena, Tiurma; Muskibah, Muskibah; Raffles, Raffles (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to find out and criticize 1) the regulation of the difference in the content of the deed minuta and the copy of the deed issued by the Notary to the parties. 2) The notary's legal responsibility for the difference in the contents of the deed and the copy of the deed issued is associated with the principle of prudence. This research uses a normative juridical method, with a conceptual approach, a legislative approach and a case approach. The analysis of legal materials is carried out by inventorying, systematizing and interpreting. The results of the research are 1) Arrangements regarding the difference in the contents of the deed minuta and copies of the deed issued by the Notary to the parties are regulated in Article 1 number 9, Article 16 paragraph 1 letters a and d and corrections in Article 51 of the UUJN. The ambiguity of the legal norms of Article 51 of the UUJN-P does not explain the substantial or non-substantial typographical errors that can be corrected, how with the copy of the deed that has been given to the parties and the provisions of Article 51 of the UUJN-P it becomes difficult to implement in the event that the witnesses no longer exist before the Notary. Legal principles that can be used as a form of settlement for differences in the minuta of the deed and copies of the deed issued by the Notary to the parties are the principle of prudence, the principle of good faith and the principle of abuse of authority. The difference between the minutes of the deed and the copy of the deed is due to the lack of caution of the Notary and typos by the Notary. 2) Notaries are also responsible, especially if degradation of deeds occurs, subject to Administrative and Civil sanctions. Recommendations to 1) Policy makers, in order to be able to regulate in detail how the Notary principle of prudence, especially on the form and nature of the renvoi in the deed and the limits of the Notary's authority over it, especially the Renvoi which is only carried out after the issuance of a copy of the Deed to protect the Notary and the parties. 2) The Notary in carrying out his obligations must prioritize the attitude of thoroughness, thoroughness, prudence, not abusing authority and good faith when making a deed so that the deed he makes can give a sense of justice to the parties. Preventive efforts that can be made by the Notary sign or paraphrase each page of the deed that is made and works based on the principle of prudence